Kesulitan Belajar Dan Membaca Pada Anak Berkebutuhan Khusus - Wiwik Depani Putri; Nazratul Fitri; Riyo Handani; Opi Andriani (Simpati, 2024)
Children with special needs are individuals with certain conditions of instability who require a special approach in education. Children with special needs often face learning and reading difficulties. Several factors that can cause these difficulties are neurological disorders, motor difficulties, visual perception difficulties, language and communication difficulties as well as lack of support and adjustments in the learning process. This research aims to dig deeper into this problem and provide an understanding of the factors that influence learning and reading difficulties in children with special needs. The keywords used in this research are children with special needs, learning difficulties, reading difficulties. The method used is qualitative with a case study approach. The research was conducted involving children with special needs, data was collected through classroom observations, interviews with parents and teachers, as well as observations of children's learning and reading progress